2010
DOI: 10.1002/jbmr.156
|View full text |Cite
|
Sign up to set email alerts
|

The role of estrogen receptor α in growth plate cartilage for longitudinal bone growth

Abstract: Estrogens enhance skeletal growth during early sexual maturation, whereas high estradiol levels during late puberty result in growth plate fusion in humans. Although the growth plates do not fuse directly after sexual maturation in rodents, a reduction in growth plate height is seen by treatment with a high dose of estradiol. It is unknown whether the effects of estrogens on skeletal growth are mediated directly via estrogen receptors (ERs) in growth plate cartilage and/or indirectly via other mechanisms such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
46
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 44 publications
7
46
1
1
Order By: Relevance
“…Patients with estrogen deficiency, caused by a mutation in the aromatase gene, as well as a man with a nonfunctional ERα, causing estrogen resistance, continued to grow after sexual maturation because of unfused growth plates (4,24,37). In addition, we have shown that mice with complete inactivation of ERα (ERα −/− ) have a similar growth plate phenotype as these patients, resulting in a sustained longitudinal bone growth (38,39). High E2 levels in late puberty induce growth plate closure and thereby cessation of growth in humans.…”
Section: Ici Acts As An Inverse Erα Agonist On the Growth Plate Heighmentioning
confidence: 81%
“…Patients with estrogen deficiency, caused by a mutation in the aromatase gene, as well as a man with a nonfunctional ERα, causing estrogen resistance, continued to grow after sexual maturation because of unfused growth plates (4,24,37). In addition, we have shown that mice with complete inactivation of ERα (ERα −/− ) have a similar growth plate phenotype as these patients, resulting in a sustained longitudinal bone growth (38,39). High E2 levels in late puberty induce growth plate closure and thereby cessation of growth in humans.…”
Section: Ici Acts As An Inverse Erα Agonist On the Growth Plate Heighmentioning
confidence: 81%
“…Western Blot was essentially performed as described previously (37). Further details are provided in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…(Box i) The cortical and (Box ii) the cancellous bone compartments as well as (Box iii) the growth plate of a long bone are depicted in the respective blue boxes. The cells responsible for the particular action along with their dependency or lack thereof on estrogens (E2) in each compartment are deduced from the respective cell-specific ERα deletion murine models of the present work and two earlier papers in which ERα was selectively deleted in osteoclasts (7) and chondrocytes (48). Red arrows point to the site at which the effect summarized in the blue boxes occurs.…”
Section: Figurementioning
confidence: 96%